The ripple effects of large-scale transport infrastructure investment - D. Persyn; Javier Barbero; J. Díaz-Lanchas; P. Lecca; G. Mandras; S. Salotti (European Commission, Joint Research Centre (JRC), 2022)
We analyse the general equilibrium effects of an asymmetric decrease in transport costs, combining a large scale spatial dynamic general equilibrium model for 267 European NUTS 2 regions with a detailed transport model at the level of individual road segments. As a case study we consider the impact of the road infrastructure investments in Central and Eastern Europe in the context of the EU cohesion policy programme. Our analysis suggests that the decrease in transportation costs benefits the regions targeted by the policy via substantial increases in GDP and exports compared to the baseline, and small increases in population. The geographic information embedded in the transport model leads to relatively large predicted benefits in peripheral countries such as Greece and Finland who hardly receive funds, but whose trade links cross Central and Eastern Europe and thus profit from the investments there. The richer, Western European non-targeted regions also enjoy a higher GDP after the investment in the East, but these effects are smaller. Thus, the policy reduces interregional disparities. There are rippled patterns in the predicted spillovers of the policy. In non-targeted countries, regions trading more intensely with regions where the investment is taking place on average benefit more compared to other regions within the same country, but also compared to neighbouring regions across an international border. Using regression analysis we uncover that regions which import intermediate inputs from Central and Eastern Europe enjoy the largest spillovers. These regions become more competitive and expand exports locally, at the detriment of other regions in the same country.
Keywords: C68; R11; R13; R15; R41; 330; transport infrastructure; economic geography; computable general equilibrium modelling